1998
DOI: 10.1046/j.1365-2648.1998.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical skills of community psychiatric nurses working with patients who have severe and enduring mental health problems: an empirical analysis

Abstract: This study describes the use of reliable scales to rate the clinical skills of mental health nurses when working with individuals and families with severe mental health problems. The Cognitive Therapy Scale and the Schizophrenia Family Work Scale were adapted for the study and were shown to have good inter-rater reliability when assessing audio-taped interviews carried out by mental health nurses during their usual course of work with patients with severe mental health problems and their families. The sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…It may simply be that travelling around congested cities is perceived as far more time‐consuming and tiring than on less busy roads. The study supports the work of Devane et al . (1998) which concludes that more accurate information is required about what proportion of time community staff spend with clients and travelling between clients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It may simply be that travelling around congested cities is perceived as far more time‐consuming and tiring than on less busy roads. The study supports the work of Devane et al . (1998) which concludes that more accurate information is required about what proportion of time community staff spend with clients and travelling between clients.…”
Section: Discussionsupporting
confidence: 93%
“…(1997) and Jackson & Stevenson (2000) remark that although professional groups may find themselves vulnerable during times of transition, there are currently unprecedented opportunities for nurses as their role is a nurturing one and central to mental health care. Devane et al . (1998) note that more research is needed into what CMHNs are currently doing and looking at the contexts in which they work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings support Hopton's (1997) conclusion that nurses require a stronger ideological base to support their claims to therapeutic efficacy. They also support Devane et al . (1998), who exposed considerable variation in the skills base of mental health nurses.…”
Section: Discussionsupporting
confidence: 88%
“…Devane et al . (1998) found great variability in the skills to which mental health nurses lay claim, and noted that although they relate well to clients, they are poor at providing feedback to them and making explicit their agendas, and do not collaborate with other healthcare personnel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1999). Another study reported the need for CPNs to acquire more specific cognitive therapy technical skills, hence suggesting the need for training in that area (Devane et al . 1998).…”
Section: Discussionmentioning
confidence: 99%